The Argument from Illusion in Gorgias’ Treatise On What Is Not (Revista Archai, 2025)
The argument from illusion which is also known as the argument from perceptual relativity or from conflicting appearances and sense-impressions, has occurred in many thinkers from antiquity to the present. The conclusions drawn from that argument are different from philosopher to philosopher. In Plato's Republic, the case of the crooked object when in water and similar cases show that there is a weakness in our nature within us revealed by the fact that our sight is liable to illusion and confusion. Aristotle's Protagoreans concluded that one's beliefs about whatever appears, let us say, cold or not cold is true and proceeded to a denial of the principle of contradiction. In Sextus Empiricus, it justifies a scepticism about belief and knowledge in general. In Descartes, it justifies a scepticism about the senses. In Ayer, the argument from illusion proves the existence of sense-data. My intention herewith is to show how Gorgias uses the argument from illusion treating it as related to the problems of the philosophy of perception. No attention has been paid to this issue in the literature.